Analisis Pengaruh Partai Politik Terhadap Pembangunan Demokrasi di Indonesia - Ribka Sri Rezeki Simanjutak; Rian Rambu Raya; Rizal Al Birra (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Abstract. This research aims to analyze the influence of political parties on the development of democracy in Indonesia. Indonesian democracy, as a country with a long history of political dynamics, is greatly influenced by the role and performance of political parties. This research uses a quantitative approach with a literature review method to examine various aspects, including the function of political parties in the election process, public policy formation, and their contributions to supporting or hindering the democratization process. The results show that political parties play a crucial role in strengthening democratic institutions through political representation and public participation. However, the findings also indicate signs of fraud and dishonesty by political parties in submitting LADK improvements to the KPU, and weak cadre formation that can hinder the development of democracy. This research concludes that to strengthen democracy in Indonesia, political party reforms are needed, focusing on transparency, accountability, and the enhancement of inclusive political participation. Keywords: Influence of Political Parties, Democratic Development, Political Dynamics, Role of Political Parties, Performance of Political Parties Abstrak. Penelitian ini bertujuan untuk menganalisis pengaruh partai politik terhadap pembangunan demokrasi di Indonesia. Demokrasi Indonesia, sebagai negara yang memiliki sejarah panjang dalam dinamika politik, sangat dipengaruhi oleh peran dan kinerja partai politik. Penelitian ini menggunakan pendekatan kuantitatif dengan metode kepustakaan untuk mengkaji berbagai aspek yang mencakup fungsi partai politik dalam proses pemilihan umum, pembentukan kebijakan publik, serta kontribusi mereka dalam mendukung atau menghambat proses demokratisasi. Hasil penelitian menunjukkan bahwa partai politik memiliki peran krusial dalam memperkuat institusi demokrasi melalui representasi politik dan partisipasi masyarakat. Namun, temuan juga mengindikasikan adanya indikasi kecurangan dan ketidakjujuran partai politik dalam mengajukan perbaikan LADK kepada KPU, dan lemahnya kaderisasi yang dapat menghambat perkembangan demokrasi. Penelitian ini menyimpulkan bahwa untuk memperkokoh demokrasi di Indonesia, diperlukan reformasi partai politik yang fokus pada transparansi, akuntabilitas, dan peningkatan partisipasi politik yang inklusif. Kata Kunci: Pengaruh Partai Politik, Pembangunan Demokrasi, Dinamika Politik, Peran Partai Politik, Kinerja Partai Politik